Transforming Village Economy through Introduction to Basic Accounting and Simple Financial Reports: A Case Study - Lingga, Ita Salsalina; Carolina, Yenni; Susilawati, Christine Dwi Karya; Tin, Se (Universitas Mathla'ul Anwar Banten, 2025)
Micro, Small, and Medium Enterprises (MSMEs) and rural communities play a pivotal role in Indonesia's economy but often face challenges in financial management and accounting practices. Limited accounting literacy results in the inability to produce accurate financial reports, hindering access to financing and economic decision-making. This community service program aimed to enhance the understanding of basic accounting principles and simple financial reporting among the people of Jatiendah Village and local MSMEs. The program utilized interactive lectures, practical simulations, and mentoring to implement financial recording. The results indicated improved participant comprehension of fundamental accounting concepts and their ability to create simple financial reports. This program not only empowered participants to manage finances more effectively but also contributed to local economic empowerment. By delivering practical and applicable accounting education, the program is expected to strengthen community-based financial governance and promote MSME sustainability.